The Environmental Dimension of the Cohesion Policy and the Management of Investments to Aimed the Reducing Pollutants in the Area of Water and Sewage Management - Ewa BIEŃ (Communications of International Proceedings, 2022)
The necessity to reduce the emission of substances into the natural environment as well as limited resources continue to pose a challenge in the process of implementing the principles of sustainable development in the economy. Poland has been taking advantage of the opportunities offered by EU funds for over 20 years. The resources from the Cohesion Fund (CF) and the European Regional Development Fund (ERDF) contracted under individual national programs are sources of financing that provided and still provide an important opportunity to achieve the objectives of the cohesion policy, including environmental protection, tailored to the specificity of the country and its regions. The publication analyzes how infrastructure investments implemented by municipalities using EU funds from the ERDF and CF contribute to pollution reduction in the area of water and sewage management in individual voivodships and affect the quality of life of their inhabitants. It should be emphasized that without EU funds the achieved scope of these activities would not have been possible. Quantitative methods, including classical descriptive statistics and taxonomic methods based on linear ordering of objects, were used to analyze the collected data. The stated aim of the publication was examined both in general and in the environmental dimension using result and product indicators broken down into categories by regions.
Keywords: water and sewage management; pollution reduction; EU funds; investments